2015
DOI: 10.1098/rsif.2015.0320
|View full text |Cite
|
Sign up to set email alerts
|

Microbuckling of fibrin provides a mechanism for cell mechanosensing

Abstract: Biological cells sense and respond to mechanical forces, but how such a mechanosensing process takes place in a nonlinear inhomogeneous fibrous matrix remains unknown. We show that cells in a fibrous matrix induce deformation fields that propagate over a longer range than predicted by linear elasticity. Synthetic, linear elastic hydrogels used in many mechanotransduction studies fail to capture this effect. We develop a nonlinear microstructural finite-element model for a fibre network to simulate localized de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
200
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 102 publications
(224 citation statements)
references
References 38 publications
(92 reference statements)
23
200
1
Order By: Relevance
“…The results from this study support the growing body of experimental and theoretical work that indicates that the fibrous nature of biological gels is responsible for enhanced long-distance cell mechanosensing compared to nonfibrous gels [14][15][16][17]30,[46][47][48]. Several of these theoretical studies have found that the mechanosensing length scale of a cell increases when fibers are accounted for in the model [14,30,46,48].…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…The results from this study support the growing body of experimental and theoretical work that indicates that the fibrous nature of biological gels is responsible for enhanced long-distance cell mechanosensing compared to nonfibrous gels [14][15][16][17]30,[46][47][48]. Several of these theoretical studies have found that the mechanosensing length scale of a cell increases when fibers are accounted for in the model [14,30,46,48].…”
Section: Discussionsupporting
confidence: 74%
“…If the surrounding material was represented instead by a homogeneous nonlinear strain-hardening material, then the stresses rapidly decayed a short distance away from the cells and no mechanical communication occurred between the two cells. Another key property of the networks that facilitates fiber alignment and the transmission of long-range mechanical signals is the low compressive resistance of the fibers (relative to the tensile stiffness), which Notbohm et al also reported and referred to as microbuckling [30]. In this context, microbuckling does not refer to a mechanism of failure, but instead means that less energy is needed for fibers in the network to compress in order to accommodate the realignment of other network fibers in tension.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations